Poudarki v slovenskem medijskem govoru z vidika izbranih jezikovnih enot - Huber, Damjan (Jezik in slovstvo, 2022)
The paper deals with sentence stress in media speech, with particular regard to interrogatives, nugatory elements and affirmatives, as well as demonstrative pronouns, comparatives and superlatives. Stress is dealt with as an important marker and organiser of speech, as emphasised content in the flow of speech, and there is a focus on the syllables in words within particular segments that the interlocutors and listeners recognise as highlighted in some way. A comparative analysis of the occurrence of stresses in selected language units, based on a corpus of spoken texts from Slovenian television broadcasts, shows that TV presenters primarily stress interrogatives, whereas their guests (politicians) primarily stress nugatory elements and demonstrative pronouns.
Keywords: affirmative; demonstrative pronoun; interrogative; kazalni zaimek; nikalnica; nugatory element; poudarek; pritrdilnica; sentence stress; Slovene; slovenščina; vprašalnica